Efektivitas Aplikasi Pupuk Organik Cair Limbah Kulit Pisang dan Pupuk Urea Terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq.) di Pembibitan Pre-Nursery - Mahdalena; Asiah Wati; Lubis (Agrifarm : Jurnal Ilmu Pertanian, 2025)
The purpose of this study was to determine the effect of Banana Peel Waste POC and Urea Fertilizer and the interaction of the two treatments on the growth of oil palm seedlings in the Pre-nursery. The study was conducted for 4 months, starting from March 2025 preparation to June 2025 the final data collection and took place at the Research Field of the Faculty of Agriculture, Widya Gama Mahakam University Samarinda, Jalan Wahid Hasyim, Sempaja Village, North Samarinda District, East Kalimantan. The research method used a Factorial Randomized Block Design (RAK) consisting of 2 factors with 3 replications. The first factor is Banana Peel Waste POC (P) which consists of 4 levels, namely: P0 (Control), P1 (50 ml/polybag), P2 (75 ml/polybag) P3 (100 ml/polybag The second factor is Urea Fertilizer (U) which consists of 4 levels, namely: U0 (Control), U1 (8 g/polybag), U2 (10 g/polybag), and U3 (12 g/polybag). The observation variables are plant height growth, stem diameter and number of leaves. The results showed that Banana Peel Waste Liquid Organic Fertilizer (POC) significantly affected all parameters at 90 days after planting (HST) with the best dose of 50 ml/polybag. Urea fertilizer significantly affected all parameters at 60 and 90 days after planting at a dose of 12 g/polybag. Meanwhile, the interaction between Banana Peel Waste Liquid Organic Fertilizer (POC) and Urea did not significantly affect all observed parameters.